Poetic Characteristics of Chronotopy of Photos in Isajon Sultan's Novel "Free" - Hasanova Hikmatoy Akhrorjon qizi (International Journal on Integrated Education, 2021)
The article explores the unique role of the artistic chronotope in Isajon Sultan's novel "Free". In it, the writer also re-perceives a number of images in the image of Freedom. Also, perceptions of the universe and man are important in that they focus on understanding the protagonist in the language of different phenomena.